THE EFFECT OF AGENCY ACCOUNTING SYSTEM AND INTERNAL CONTROL ON THE QUALITY OF FINANCIAL STATEMENTS - Bunga Roy Apriliya; JMV. Mulyadi; Suyanto (ZILLZELL MEDIA PRIMA, 2023)
This study aims to determine the influence of the agency's accounting system and internal control on the quality of financial statements at the Directorate General of Learning and Student Affairs of the Ministry of Research, Technology and Higher Education using two variables, namely the agency's accounting system, internal control, and the quality of financial statements. The sampling technique uses purposive sampling, the criteria are employees / officials who work to handle the Accounting System of the Agency, namely SAK and SIMAK-BMN operators, Head of Subbag, Head of Bag and Assistant Director II for General Administration and Finance who handles the preparation of Financial Statements. The questionnaire used in this study was 102 respondents. Before using multiple linear regression analysis, first conduct data quality tests (validity tests and reliability tests) and classical assumption tests (normality tests, multicolonicity tests and heteroscedasticity tests) with the SPSS version 21 program. The results showed that the agency's accounting system and internal control have a positive and significant effect on the quality of financial statements so that the agency's accounting system and internal control need to be applied in the preparation of financial statements within government agencies.